Analysis of Factors Affecting E-Health Aplication User Satisfaction At PT Pra - Dendry Asharrudin*; Ahmad Nurul Fajar (Riwayat: Educational Journal of History and Humanities, 2023)
The Health Industry is an industry that is important in human life because it greatly influences the welfare and health of the community. In providing health services, in addition to maintaining the satisfaction of managers, they must also maintain patient safety. Information technology can be used as a means to support activities carried out in the health industry, for example in marketing health services, the use of technology can be used to be able to compete in advancing these health service companies by marketing health services using information technology. The use of information technology is now starting to spread to smartphones. Mobile applications began to be used to facilitate an activity without having to use a computer. Advances in supporting technology, including computer hardware and software, encourage and develop various types of telemedicine and e-Health systems for various applications. PT PRA also encourages public understanding of the future of digital health services, namely the elements that encourage digitization of health, the impact of technology on pathology as a science that studies disease and its formation, to the transformation of digital laboratory clinics. In supporting the company's operations in responding to consumer needs for safe health services, PT PRA has developed an E-Health application system for consumers. Customer satisfaction is very important for the sustainability of PT PRA Company. This has a strong positive relationship with customer loyalty and intention to reuse PT PRA services. Customer satisfaction is one of the goals of using the PT PRA Mobile application because it is very valuable for increasing revenue. The aim of the researchers to carry out the research was to analyze the factors that influence the Satisfaction of Mobile E-Health Users at PT PRA is to find out the factors that significantly influence PT PRA's customer satisfaction with PT PRA's E-Health application. This research was conducted in all PT PRA branches. The research object is 100 PT PRA customers who will fill out a questionnaire about PT PRA's E-Health application. The data analysis technique used in this study is to use the Smart-PLS software. The variables used are information quality, system quality, service quality, and Advanced Capabilities Expected from the System. The results of this study can be used as a reference for application development and additional features that are expected to increase customer satisfaction. The results of this study indicate that the three variables, namely system quality, information quality, and expected advanced capabilities of the tested system have a significant effect on customer satisfaction at PT PRA while service quality does not have a significant effect on customer satisfaction at PT PRA.